Preliminary Biochemical Study for Three Extracts of Lycium sp. Plant - Jasim Abbas, Jasim Abbas; A. Al – Imarah, Eman; A. Al-yasiry, Ali; K.Auda, L. (University of Thi-Qar Journal of Science, 2009)
An aquous hot , cold and hot ethanolic extracts fraction for Lycium species have been prepared. Qualitative tests have been carried out for detection of their general chemical composition ,and UV-Visible spectra were also obtained .The antibacterial activity of the extracts was tested by the well diffusion method .Human blood cells were used to determine cytotoxicity for the extracts in concentration 500 mg/ml . No cytotoxic effects were observed by this concentration,and this is considered the first step in the work positively and in the continuity of testing the extracts on human by pharmacy and medicine colleges.